Answer:
x = t
y = -t
z = (17-6t)/5
Explanation:
First we will write down Equation 1 and Equation 2
4x-2y+5z = 17------(1)
x + y = 0--------(2)
Since we are asked to express our answer in terms of the parameter t so lets suppose x = t and y = -t
Now substitute the value of x and y in equation (1) we get
4(t) -2(-t) +5z = 17
6t + 5z = 17
5z = 17 -6t
z = (17-6t)/5
hence we get the following answer
x = t
y = -t
z= (17-6t)/5
we can also verify our answer by substituting the values of x ,y and z in any of the two equations above, for example lets substitute these values in equation 1
4(t) -2(-t) + 5((17-6t)/5)) = 17
6t + 17 -6t = 17
6t -6t = 17 -17
0 = 0